Foxb1 Regulates Negatively the Proliferation of Oligodendrocyte Progenitors - Yuanfeng Zhang; Yuanfeng Zhang; Elti Hoxha; Tianyu Zhao; Xunlei Zhou; Gonzalo Alvarez-Bolado (Frontiers Media S.A., 2017)
Oligodendrocyte precursor cells (OPC), neurons and astrocytes share a neural progenitor cell (NPC) in the early ventricular zone (VZ) of the embryonic neuroepithelium. Both switch to produce either of the three cell types and the generation of the right number of them undergo complex genetic regulation. The components of these regulatory cascades vary between brain regions giving rise to the unique morphological and functional heterogeneity of this organ. Forkhead b1 (Foxb1) is a transcription factor gene expressed by NPCs in specific regions of the embryonic neuroepithelium. We used the mutant mouse line Foxb1-Cre to analyze the cell types derived from Fobx1-expressing NPCs (the Foxb1 cell lineage) from two restricted regions, the medulla oblongata (MO; hindbrain) and the thalamus (forebrain), of normal and Foxb1-deficient mice. Foxb1 cell lineage derivatives appear as clusters in restricted regions, including the MO (hindbrain) and the thalamus (forebrain). Foxb1-expressing NPCs produce mostly oligodendrocytes (OL), some neurons and few astrocytes. Foxb1-deficient NPCs generate mostly OPC and immature OL to the detriment of neurons, astrocytes and mature OL. The axonal G-ratio however is not changed. We reveal Foxb1 as a novel modulator of neuronal and OL generation in certain restricted CNS regions. Foxb1 biases NPCs towards neuronal generation and inhibits OPC proliferation while promoting their differentiation.